2015
DOI: 10.1097/inf.0000000000000667
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Sufficiency and Staphylococcus Aureus Infection in Children

Abstract: Vitamin D promotes epithelial immunity by upregulating antimicrobial peptides (AMPs), including LL-37, that have bactericidal activity against Staphylococcus aureus. We found that children with vitamin D deficiency or insufficiency [25(OH)D <30 ng/mL] were more likely to present with recurrent, rather than primary, S. aureus skin or soft tissue infection (SSTI). Vitamin D sufficiency may be one of a myriad of host and environmental factors that can be directly impacted to reduce the frequency of S. aureus SSTI. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
1
14
0
2
Order By: Relevance
“…Moreover, VDR gene polymorphisms can be important for susceptibility to urinary tract infection and renal scar formation [ 275 ]. In an USA study a similar association was observed between skin or soft tissue infections by Staphylococcus aureus strains and vitamin D levels [25(OH)D < 30 ng/ml] in 202 children [ 276 ]. Other authors reported similar findings in children with acute diarrhea [ 277 ], otitis [ 277 ], rotavirus infection [ 278 ], malaria [ 279 ], leishmaniosis [ 280 ], hepatitis C [ 281 ], or sepsis [ 282 ].…”
Section: Extraskeletal Actions Of Vitamin Dmentioning
confidence: 59%
“…Moreover, VDR gene polymorphisms can be important for susceptibility to urinary tract infection and renal scar formation [ 275 ]. In an USA study a similar association was observed between skin or soft tissue infections by Staphylococcus aureus strains and vitamin D levels [25(OH)D < 30 ng/ml] in 202 children [ 276 ]. Other authors reported similar findings in children with acute diarrhea [ 277 ], otitis [ 277 ], rotavirus infection [ 278 ], malaria [ 279 ], leishmaniosis [ 280 ], hepatitis C [ 281 ], or sepsis [ 282 ].…”
Section: Extraskeletal Actions Of Vitamin Dmentioning
confidence: 59%
“…aureus vaccine challenges bone marrow dendritic cells and macrophages, which normally kill S. aureus, were found to be a safe haven for S. aureus strains that displayed high activity of the Agr quorum-sensing system (O'Keeffe et al, 2015). Finally, the staphyloccidal activity of dendritic cells is enhanced by vitamin D and patients that are vitamin D deficient are more likely to have more nasal carriage, skin infections, and more invasive infections (Olsen et al, 2012;Thomason et al, 2015;van der Does et al, 2014;Wang et al, 2015). Some of the antibodies tested in clinical trials have aimed at staphylococcal adhesins (Fowler and Proctor, 2014;DeJonge et al, 2007;Weems et al, 2006).…”
Section: Ra Proctormentioning
confidence: 99%
“…9 Some observational studies report an association between vitamin D deficiency and increased infectious diseases. [10][11][12] Randomized trials, however, show conflicting results and few involve infants. [13][14][15] Because infections are a major cause of early childhood morbidity, the effect of vitamin D supplementation is of great interest.…”
mentioning
confidence: 99%